The effect of sensory playbook 30 days on the development of children aged 6-36 months in Ngawen District, Gunung Kidul Regency - Widya Octaviana; Hanifah Sarah Nur Laila Aji; Nabila Khairunisa Azzahra; Nita Andayani; Dwiky Setyo Ningrum; Anes Rafiqa Aprilya; Fatimah Rachmawati; Nafisa Putri Nailul Muna; Fauziah Rahmawati; Nudiya Salwa Syifa Kamila; Rufidah Maulina; Siti Nurhidayati (Journal of Health Technology Assessment in Midwifery, 2022)
Background: Sensory Play is an active play facility that involves touch, taste, smell, sight, hearing, vestibular, and proprioception. Sensory play can support the development of speech and language, gross and fine motor skills, cognitive abilities, and social interaction, especially with their peers. The purpose of this study was to analyze the effect of the sensory playbook 30 days using an approach of sensory play on the development of children aged 6-36 months in Ngawen District, Gunung Kidul Regency. Method: This research is a descriptive study using quantitative methods to measure the level of children development with a pre-test and post-test approach using the Developmental Pre Screening Questionnaire (KPSP). An intervention in the form of sensory play from the book "30 Days of Sensory Play Ideas to Support Toddler Growth" was also used Results: Based on the results of the study showed the Chi-Square test p value < 0.000 where p < 0.005. Thus it can be concluded that there is an influence Â from the sensory playbookÂ  on the development of children aged 6 - 36 months in Ngawen District, Gunung Kidul Regency. Conclusion: The Intervention of the 30 Days Idea Sensory Play Book has an effect on the development of children aged 6 - 36 months showing an influence on development which is seen through the interpretation of dubious KPSP results or deviations from being age-appropriate. Community health center or midwife can suggest the parents to use sensory play in order to improve their children's growth and development.